High-performance lithium iron phosphate composite material and preparation method thereof
By modified iron phosphate and carbon nanotubes, and combined with the method of irradiation of UV lamps and other materials, the problem of insufficient adhesion between lithium iron phosphate orthopedic materials and aluminum foil, and realized the high -performance iron phosphate composite material Preparation significantly improves the electrochemical properties and stability of the battery.
Patent Information
- Application Number
- CN202411534671.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-31
AI Technical Summary
In the prior art, the adhesion between the lithium iron phosphate positive electrode material and the aluminum foil is poor, resulting in material dropout, depowder, poor flexibility and a decrease in energy density per unit volume, affecting battery performance.
By modified treatment on lithium iron phosphate and carbon nano tubes, combined with the use of bastylishaxyl ether and chloroform to form a premier, and react with other materials after irradiation under ultraviolet light to form high -performance lithium iron phosphate composite materials Essence This method improves the adhesion and conductivity of materials.
The stable adhesion between lithium iron phosphate composite materials and aluminum foil, reducing the falling of the electrode particles, significantly improved the electrochemical properties and stability of the battery.
Smart Images

Figure BDA0005111260170000021 
Figure BDA0005111260170000031 
Figure BDA0005111260170000081
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular, relates to a high-performance lithium iron phosphate composite material and a preparation method thereof. Background Art
[0002] With the increasing prominence of energy crisis and environmental pollution, developing new energy and solving storage problems have become the main tasks at present. High-performance energy storage equipment is an important carrier for the utilization of new energy. Green and environmentally friendly lithium-ion batteries are widely welcomed by people because of their suitable working voltage, long cycle life, high energy density, and low self-discharge. As one of the key materials of lithium-ion batteries, positive electrode materials play a decisive role in the capacity of the entire lithium-ion battery, and are also becoming the focus of research and development, industrialization and large-scale application in the field of new energy materials in various countries. Compared with other materials, lithium iron phosphate has the advantages of good thermal stability, high safety performance, low price, and environmental friendliness, and is favored by people, becoming one of the positive electrode materials with the most development potential.
[0003] The existing technology often uses PVDF binder to bond conductive carbon black and lithium iron phosphate as positive electrode materials. This type of positive electrode material has poor adhesion to aluminum foil, resulting in material shedding, powder shedding, poor overall flexibility of the positive electrode sheet, and reduced unit volume energy density of the sheet, which are all detrimental to the performance of the final finished battery. At the same time, the bonding strength between the conductive agent and the conductive active material is insufficient, and vibration can easily cause the electrode particles to fall off, resulting in capacity decay. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a high-performance lithium iron phosphate composite material and a preparation method thereof.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A method for preparing a high-performance lithium iron phosphate composite material comprises the following steps:
[0007] (1) at room temperature and under nitrogen protection, the modified lithium iron phosphate, the modified carbon nanotubes, dimethyl benzoate and chloroform were stirred until they were uniformly mixed, then irradiated under a 365 nm ultraviolet lamp for 15 min, and finally dried to obtain a premix;
[0008] (2) The premix, glacial acetic acid, polyethylene glycol and DMF (N,N-dimethylformamide) are mixed evenly, and then the temperature is raised to 70-80°C and stirred for reaction for 4-6 hours. After the reaction is completed, it is cooled to room temperature, filtered, washed with anhydrous ethanol for 3-5 times, immersed in zinc acetate solution, allowed to stand for 20 hours, filtered, washed with anhydrous ethanol for 3-5 times, and vacuum dried at 80°C for 8 hours to obtain a high-performance lithium iron phosphate composite material.
[0009] Furthermore, the modified lithium iron phosphate in step (1) is prepared by the following steps:
[0010] S1. Blow nitrogen into a dry three-necked flask to expel air and moisture from the flask, then add benzotriazole and chloroform, stir evenly and heat to 65°C, then slowly add KH560 (3-glycidyloxypropyltrimethoxysilane), stir and react at 65°C for 5h after the addition is complete, cool to room temperature after the reaction is completed, and distill under reduced pressure to obtain intermediate 1; the dosage ratio of benzotriazole, KH560 and chloroform is 13.7g:19.9mL:110mL;
[0011] Under heating conditions, the molar ratio of benzotriazole and KH560 is controlled to be 1.2-1.3:1, then the -NH- of benzotriazole and the epoxy group of KH560 react, and the reaction process is as follows:
[0012]
[0013] S2, nitrogen was blown into a dry three-necked flask to expel air and moisture in the flask, and then intermediate 1, 10% sodium hydroxide solution and benzene were added, stirred evenly and heated to 60°C, and epoxybutene was slowly added. After the addition was completed, the mixture was stirred and reacted at 60°C for 5h. After the reaction was completed, the mixture was cooled to room temperature and distilled under reduced pressure to obtain intermediate 2; the usage ratio of intermediate 1 to epoxybutene was 30.2g:5.4mL;
[0014] Under heating and base catalysis conditions, the -OH of intermediate 1 reacts with the epoxy group of epoxybutene. The reaction process is as follows:
[0015]
[0016] S3, lithium carbonate, ferrous oxalate dihydrate, and ammonium dihydrogen phosphate are mixed evenly to obtain a reactant, which is set aside, and then the reactant, polyethylene glycol, and deionized water are stirred for 12 hours, then filtered, vacuum dried for 12 hours, and finally calcined at 700°C for 10 hours under nitrogen protection, and naturally cooled to room temperature to obtain lithium iron phosphate; lithium iron phosphate and deionized water are added to a dry three-necked flask, stirred evenly, and concentrated hydrochloric acid is slowly added to adjust the pH value of the system to 5, then the temperature is raised to 65°C, and The mixed solution of DMF and intermediate 2 was stirred and reacted at 65°C for 10 hours, and finally cooled to room temperature, filtered, washed with anhydrous ethanol 5 times, and dried at 80°C for 12 hours to obtain modified lithium iron phosphate; the dosage ratio of lithium carbonate, ferrous oxalate dihydrate, and ammonium dihydrogen phosphate was 7.4g:17.8g:11.5g; the dosage ratio of reactants, polyethylene glycol and deionized water was 36g:7.2g:220mL; the dosage ratio of lithium iron phosphate to intermediate 2 was 20:1.
[0017] Intermediate 2 contains oily silaneoxy groups, which can hydrolyze and condense to form Si-O-Si and Si-OH. Si-OH can form covalent bonds with hydroxyl groups on the surface of lithium iron phosphate and cross-link to form modified lithium iron phosphate. The dispersion of the modified lithium iron phosphate is greatly improved, and it can play a more full role.
[0018] The surface of the modified lithium iron phosphate also has carbon-carbon double bonds, hydroxyl groups and benzotriazole structures. The hydroxyl groups can produce hydrogen bond interactions with the hydroxyl groups in the polyethylene glycol adhesive, so the lithium iron phosphate composite material has good adhesion and is not easy to fall off. At the same time, the three nitrogen atoms in the benzotriazole structure are parallel to the benzene ring, which has a strong coordination ability and can form a stable complex with the aluminum on the aluminum foil current collector through coordination bonds, which allows the lithium iron phosphate composite material to adhere to the aluminum foil for a long time and not fall off easily, thus playing a role.
[0019] Furthermore, the modified carbon nanotubes in step (1) are prepared by the following steps:
[0020] Add carbon nanotubes and deionized water to a dry three-necked flask, stir evenly, then slowly add concentrated hydrochloric acid to adjust the pH value of the system to 5, then heat to 65°C, add a mixed solution of anhydrous ethanol and γ-mercaptopropyltrimethoxysilane, continue stirring at 65°C for 10 hours, finally cool to room temperature, filter, wash with anhydrous ethanol 5 times, and dry at 80°C for 12 hours to obtain modified carbon nanotubes; the dosage ratio of carbon nanotubes to γ-mercaptopropyltrimethoxysilane is 10:1.
[0021] Carbon nanotubes can form a line-contact conductive network between active materials, greatly increasing the contact between electrode particles, thereby significantly reducing the battery interface impedance and improving conductivity with a small amount of use. γ-mercaptopropyltrimethoxysilane is used to treat the surface of carbon nanotubes, so that the surface of carbon nanotubes contains mercapto groups.
[0022] The carbon-carbon double bonds on the modified lithium iron phosphate and the thiol groups on the modified carbon nanotubes undergo a click reaction under the action of benzoin dimethyl ether, so that the modified lithium iron phosphate and the modified carbon nanotubes can be well adhered together. In addition, the modified lithium iron phosphate also contains a benzotriazole structure, which enables the lithium iron phosphate composite material to adhere to the aluminum foil for a long time and is not easy to fall off. Therefore, the electrochemical performance of the corresponding battery made of the composite material of the present invention is more excellent and stable.
[0023] Furthermore, in the step (1), the usage ratio of the modified lithium iron phosphate, the modified carbon nanotubes, dimethyl benzoate and chloroform is 42 g:(11-13) g:(0.02-0.05) g:240 mL.
[0024] Furthermore, in the step (2), the mass ratio of the premix, glacial acetic acid, polyethylene glycol and DMF is 40:(1-2):(1-2):(25-35).
[0025] Furthermore, the zinc acetate solution in step (2) is obtained by mixing zinc acetate and DMF in a mass ratio of 1:(20-30).
[0026] The invention also discloses a high-performance lithium iron phosphate composite material, which is prepared according to the preparation method of the high-performance lithium iron phosphate composite material.
[0027] Beneficial effects of the present invention: There is a chemical reaction between the active material of the present invention - modified lithium iron phosphate and the conductive agent - modified carbon nanotubes, and the premix after the reaction of the two contains hydroxyl and benzotriazole structures, so there is a hydrogen bond interaction between the premix and the binder, and the adhesion between the premix and the aluminum foil current collector is excellent. Therefore, the finished battery prepared from the lithium iron phosphate composite material of the present invention has excellent and stable electrochemical performance. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] The specific steps for preparing modified lithium iron phosphate are as follows:
[0031] S1. Blow nitrogen into a 250 mL dry three-necked flask to expel air and moisture from the flask, then add 13.7 g of benzotriazole and 110 mL of chloroform, stir evenly, heat to 65°C, then slowly add 19.9 mL of KH560, stir at 65°C for 5 h, cool to room temperature, and distill under reduced pressure to obtain intermediate 1.
[0032] S2, nitrogen was blown into a dry three-necked flask to expel air and moisture in the flask, then 30.2 g of intermediate 1, 24 mL of 10% sodium hydroxide solution and 180 mL of benzene were added, stirred evenly and heated to 60°C, and then 5.4 mL of epoxybutene was slowly added. After the addition was completed, the mixture was stirred and reacted at 60°C for 5 h. After the reaction was completed, the mixture was cooled to room temperature and distilled under reduced pressure to obtain intermediate 2;
[0033] S3, 7.4g lithium carbonate, 17.8g ferrous oxalate dihydrate, 11.5g ammonium dihydrogen phosphate were mixed evenly to obtain a reactant, which was set aside, and then 36g of the reactant, 7.2g polyethylene glycol and 220mL of deionized water were stirred for 12h, then filtered, vacuum dried for 12h, and finally calcined at 700°C for 10h under nitrogen protection, and naturally cooled to room temperature to obtain lithium iron phosphate; 40g lithium iron phosphate and 300mL of deionized water were added to a 500mL dry three-necked flask, stirred evenly, and concentrated hydrochloric acid was slowly added to adjust the pH value of the system to 5, then the temperature was raised to 65°C, and a mixed solution of 10mL DMF and 2g of intermediate 2 was added, and the reaction was stirred at 65°C for 10h, and finally cooled to room temperature, filtered, washed 5 times with anhydrous ethanol, and dried at 80°C for 12h to obtain modified lithium iron phosphate.
[0034] Example 2
[0035] The specific steps of preparing modified carbon nanotubes are as follows:
[0036] Add 11g of carbon nanotubes and 200mL of deionized water into a 500mL dry three-necked flask, stir evenly, then slowly add concentrated hydrochloric acid to adjust the pH value of the system to 5, then heat to 65°C, add a mixed solution of 10mL of anhydrous ethanol and 1.1g of γ-mercaptopropyltrimethoxysilane, continue stirring at 65°C for 10h, finally cool to room temperature, filter, wash with anhydrous ethanol 5 times, and dry at 80°C for 12h to obtain modified carbon nanotubes.
[0037] Example 3
[0038] The specific steps for preparing the lithium iron phosphate composite material are as follows:
[0039] (1) 42 g of modified lithium iron phosphate, 12 g of modified carbon nanotubes, 0.03 g of benzoin dimethyl ether and 240 mL of chloroform were stirred at room temperature and nitrogen atmosphere until the mixture was uniformly mixed, then irradiated under a 365 nm ultraviolet lamp for 15 min, and finally dried to obtain a premix;
[0040] (2) The premix, glacial acetic acid, polyethylene glycol and DMF were mixed evenly, wherein the mass ratio of the premix, glacial acetic acid, polyethylene glycol and DMF was 40:1:1:30, and then the temperature was raised to 75°C and stirred for reaction for 5 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with anhydrous ethanol for 4 times, immersed in a zinc acetate solution, wherein the mass ratio of zinc acetate to DMF was 1:25, allowed to stand for 20 hours, filtered, washed with anhydrous ethanol for 4 times, and vacuum dried at 80°C for 8 hours to obtain a high-performance lithium iron phosphate composite material.
[0041] Example 4
[0042] The specific steps for preparing the lithium iron phosphate composite material are as follows:
[0043] (1) 42 g of modified lithium iron phosphate, 11 g of modified carbon nanotubes, 0.02 g of benzoin dimethyl ether and 240 mL of chloroform were stirred at room temperature and nitrogen atmosphere until the mixture was uniformly mixed, then irradiated under a 365 nm ultraviolet lamp for 15 min, and finally dried to obtain a premix;
[0044] (2) The premix, glacial acetic acid, polyethylene glycol and DMF were mixed evenly, wherein the mass ratio of the premix, glacial acetic acid, polyethylene glycol and DMF was 40:2:2:30, and then the temperature was raised to 80°C and stirred for reaction for 6 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with anhydrous ethanol for 5 times, immersed in a zinc acetate solution, wherein the mass ratio of zinc acetate to DMF was 1:30, allowed to stand for 20 hours, filtered, washed with anhydrous ethanol for 5 times, and vacuum dried at 80°C for 8 hours to obtain a high-performance lithium iron phosphate composite material.
[0045] Example 5
[0046] The specific steps for preparing the lithium iron phosphate composite material are as follows:
[0047] (1) 42 g of modified lithium iron phosphate, 13 g of modified carbon nanotubes, 0.05 g of benzoin dimethyl ether and 240 mL of chloroform were stirred at room temperature and nitrogen atmosphere until the mixture was uniformly mixed, then irradiated under a 365 nm ultraviolet lamp for 15 min, and finally dried to obtain a premix;
[0048] (2) The premix, glacial acetic acid, polyethylene glycol and DMF were mixed uniformly, wherein the mass ratio of the premix, glacial acetic acid, polyethylene glycol and DMF was 40:1.5:1.5:30, and then the temperature was raised to 70°C and stirred for reaction for 4 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with anhydrous ethanol for 3 times, immersed in a zinc acetate solution, wherein the mass ratio of zinc acetate to DMF was 1:20, allowed to stand for 20 hours, filtered, washed with anhydrous ethanol for 3 times, and vacuum dried at 80°C for 8 hours to obtain a high-performance lithium iron phosphate composite material.
[0049] Comparative Example 1
[0050] The specific steps for preparing the lithium iron phosphate composite material are as follows:
[0051] The remaining steps remain unchanged, except that the modified lithium iron phosphate in step (1) of Example 3 is replaced by lithium carbonate without any treatment, thereby preparing a lithium iron phosphate composite material.
[0052] Comparative Example 2
[0053] The specific steps for preparing the lithium iron phosphate composite material are as follows:
[0054] The remaining steps remain unchanged, except that the modified carbon nanotubes in step (1) of Example 3 are replaced by carbon nanotubes without any treatment, thereby preparing a lithium iron phosphate composite material.
[0055] Comparative Example 3
[0056] The specific steps for preparing the lithium iron phosphate composite material are as follows:
[0057] The remaining steps remain unchanged, except that the modified lithium iron phosphate in step (1) of Example 3 is replaced by untreated lithium carbonate and the modified carbon nanotubes are replaced by untreated carbon nanotubes, thereby preparing a lithium iron phosphate composite material.
[0058] Performance Testing
[0059] Preparation of positive electrode sheet: placing an aluminum foil current collector at the bottom of a cylindrical mold with an inner diameter of 14 mm, and then placing the lithium iron phosphate composite materials prepared in Examples 3-5 and Comparative Examples 1-3, drying at 95° C. for 35 min, molding at a molding temperature of 240° C. and a molding pressure of 1.4 MPa for 25 min in a nitrogen atmosphere, then heating to 520° C. at a rate of 4° C. / min and standing for 1-2 h, keeping the molding pressure unchanged and naturally cooling to room temperature to obtain the positive electrode sheet of the button battery;
[0060] Preparation of button batteries: lithium hexafluorophosphate, ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate are mixed evenly in a mass ratio of 1:2:2:2 as an electrolyte, and the positive electrode shell, positive electrode sheet, Celgard2400 separator, lithium sheet, nickel mesh, and negative electrode shell are assembled in this order and filled with the electrolyte, and the shell is sealed to assemble into a button battery.
[0061] The positive electrode sheets prepared in Examples 3-5 and Comparative Examples 1-3 were cut into small pieces of 4*10 cm and subjected to a peel strength test on a peel strength tester. The test results are shown in Table 1 below:
[0062] Table 1
[0063]
[0064] The lithium iron phosphate composite materials prepared in Examples 3-5 and Comparative Example 1 were respectively made into button batteries, and the following performance tests were performed:
[0065] (1) Safety performance test of lithium iron phosphate battery: According to GB / T 31485-2015 standard, overcharge, over discharge and puncture test were carried out and all passed;
[0066] (2) Conduct cycle performance test of lithium iron phosphate battery in accordance with GB / T 31484-2015 standard;
[0067] (3) Carry out charge and discharge experiments at 25°C and 1C current density, and test the initial discharge capacity using the Xinwei battery testing system BTS-3000 to evaluate the electrical performance;
[0068] (4) Place the battery in an environment of 30kHz ultrasonic vibration for 50h, and conduct charge and discharge experiments at 25°C and 1C current density. Record the vibration damage rate = (1-discharge capacity after vibration / initial discharge capacity) × 100% to evaluate the vibration resistance.
[0069] The test results of all items are shown in Table 2 below:
[0070] Table 2
[0071]
[0072] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0073] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a high-performance lithium iron phosphate composite material, characterized in that: The following steps are involved: (1) stirring the modified lithium iron phosphate, modified carbon nanotubes, dimethyl benzoate and chloroform at room temperature under nitrogen protection, irradiating under a 365 nm ultraviolet lamp for 15 min, and drying to obtain a premix; (2) mixing the premix, glacial acetic acid, polyethylene glycol and DMF, heating to 70-80° C. and stirring for 4-6 hours, cooling, filtering, washing, immersing in a zinc acetate solution, standing, filtering, washing and drying to obtain a high-performance lithium iron phosphate composite material; Wherein, the modified lithium iron phosphate in step (1) is prepared by the following steps: S1. After nitrogen is blown into the flask, benzotriazole and chloroform are added, the temperature is raised to 65°C with stirring, KH560 is added, the reaction is carried out at 65°C for 5h, the reaction is cooled, and the intermediate 1 is obtained by distillation under reduced pressure; S2, after nitrogen blowing into the flask, add intermediate 1, 10% sodium hydroxide solution and benzene, stir and heat to 60°C, add epoxybutene, react at 60°C for 5h, cool, and distill under reduced pressure to obtain intermediate 2; S3, lithium carbonate, ferrous oxalate dihydrate, and ammonium dihydrogen phosphate are mixed to obtain a reactant; the reactant, polyethylene glycol, and deionized water are stirred, filtered, dried, calcined at 700° C. for 10 h, and cooled to obtain lithium iron phosphate; lithium iron phosphate and deionized water are added to a flask, the pH is adjusted, the temperature is raised to 65° C., DMF and intermediate 2 are added, the reaction is carried out for 10 h, the reaction is cooled, filtered, washed, and dried to obtain modified lithium iron phosphate; The modified carbon nanotubes in step (1) are prepared by the following steps: Add carbon nanotubes and deionized water into a flask, adjust the pH value of the system to 5 after stirring, heat to 65°C, add anhydrous ethanol and γ-mercaptopropyltrimethoxysilane, stir at 65°C for 10 hours, cool, filter, wash and dry to obtain modified carbon nanotubes.
2. The method for preparing a high-performance lithium iron phosphate composite material according to claim 1, characterized in that: The usage ratio of benzotriazole, KH560 and chloroform in step S1 is 13.7 g:19.9 mL:110 mL.
3. The method for preparing a high-performance lithium iron phosphate composite material according to claim 1, characterized in that: The usage ratio of intermediate 1 and epoxybutene in step S2 is 30.2 g:5.4 mL.
4. The method for preparing a high-performance lithium iron phosphate composite material according to claim 1, characterized in that: The usage ratio of lithium carbonate, ferrous oxalate dihydrate, and ammonium dihydrogen phosphate in step S3 is 7.4g:17.8g:11.5g; the usage ratio of reactants, polyethylene glycol, and deionized water is 36g:7.2g:220mL; and the usage ratio of lithium iron phosphate to intermediate 2 is 20:
1.
5. The method for preparing a high-performance lithium iron phosphate composite material according to claim 1, characterized in that: The usage ratio of carbon nanotubes to γ-mercaptopropyltrimethoxysilane is 10:
1.
6. The method for preparing a high-performance lithium iron phosphate composite material according to claim 1, characterized in that: In the step (1), the usage ratio of modified lithium iron phosphate, modified carbon nanotubes, benzoin dimethyl ether and chloroform is 42g:(11-13)g:(0.02-0.05)g:240mL.
7. The method for preparing a high-performance lithium iron phosphate composite material according to claim 1, characterized in that: In the step (2), the mass ratio of the premix, glacial acetic acid, polyethylene glycol and DMF is 40:(1-2):(1-2):(25-35).
8. The method for preparing a high-performance lithium iron phosphate composite material according to claim 1, characterized in that: The zinc acetate solution in step (2) is obtained by mixing zinc acetate and DMF in a mass ratio of 1:(20-30).
9. A high-performance lithium iron phosphate composite material, characterized in that: The high-performance lithium iron phosphate composite material is prepared according to the preparation method of any one of claims 1-8.
Citation Information
Patent Citations
Preparing method of highly conductive lithium iron phosphate anode material of lithium ionic cell
CN101335347A
Modified lithium iron fluorosulphate positive electrode material of low-temperature lithium battery and preparation method thereof
CN108063230A
Positive electrode and electrochemical device comprising same
CN113782708A
Preparation method of dry-method solid-state battery and dry-method solid-state battery
CN117878421A
Carbon-coated lithium iron phosphate positive electrode material and preparation method thereof
CN119447302A
Cited By
High-performance lithium iron phosphate positive electrode material and preparation method thereof
CN120622444A